Maximizing Multimodal Literacies for Listening and Pronunciation Purposes Using YouTube Resources - Diah Kristina (LINGUA: Jurnal Bahasa dan Sastra, 2019)
Abstract: YouTube resources have contributed significantly to the language learning especial- ly for multimodal literacies including listening and pronunciation. By using different kinds of mode, learners are exposed to more natural and received pronunciation of audiovisual texts in English. Minimal pairs, word transition, intonation, word stress combined with facial expres- sions, body language, eye contact, pose, pictures, photographs, musical instrument as back- grounding illustration have been a rich multimodal source to activate students’ awareness on how meaning-making efforts are not solely constructed verbally. In a more complex digitalized world, technology has provided a more natural setting of communication that students need to be aware of and make use to substitute the limited availability of native speakers especially in remote areas of extended Indonesian archipelago.Keywords: YouTube, multimodal literacies, minimal pairs, word transition, pose.Abstrak: YouTube telah banyak menyumbangkan materi pembelajaran bahasa bagi proses belajar mengajar terutama aspek literasi multimodal termasuk listening (menyimak) dan pro- nunciation (pengucapan). Dengan menggunakan berbagai mode, pembelajar dihadapkan pada pengucapan ekspresi dalam teks audiovisual berbahasa Inggris yang bersifat lebih alamiah. Minimal pairs (pasangan kata yang memiliki kemiripan bunyi), word transition (bunyi khusus sebagai pelumas dalam merangkai dua kata), intonasi, tekanan kata yang dikombinasikan den- gan ekspresi wajah, bahasa tubuh, kontak mata, posetubuh, gambar, foto, iringanmusik,meru- pakan sumber multimodal yang kaya untuk membuat siswa sadar bahwa pembentukan makna tidak semata-mata dikonstruksi secara verbal. Di era digital yang konpleks ini teknologi telah memungkinkan munculnya komunikasi dengan setting yang lebih alamiah yang mengharuskan siswa memanfaatkan kekayaan sumber pembelajaran tersebut sebagai pengganti keberadaan native speaker terutama di daerah terpencil di kepulauan Nusantara (Indonesia) yang maha luas ini. Kata-kata Kunci: YouTube, literasi multimodal, pasangan kata yang memiliki kemiripan bunyi, transisi kata, pose.